Green Synthesis of ZnO Nanoparticles with Papaya Leaf Extract (Carica papaya L.) as a Reductor and its Application on Cotton Fabrics (Indonesian Journal of Chemical Science, 2022)
ZnO nanoparticles have great applications such as photocatalysts and have antibacterial activity and hydrophobic properties. In this research, green synthesis with papaya leaves extracts as a reducing agent for ZnO nanoparticles that applicated on cotton fabric with pad dry-cure method. ZnO nanoparticle coating was carried out at concentrations of 3%, 6%, and 9%. Characteristics resulting from FT-IR and XDR identified ZnO nanoparticles from the synthesis with papaya leaf extract have a crystallinity level of 76.97% with a crystalline size of 39.60 nm. Application of ZnO nanoparticles on fabric showed an increase in the hydrophobic properties of the fabric and good antibacterial activity on the Staphylococcus aureus (gram-positive bacteria) and Escherichia coli (gram-positive bacteria). The highest contact angle of the ZnO nanoparticle-coated fabric is shown in the concentration of 3% which is 113°. The highest antibacterial activity was shown at the concentration of the largest 9% in Staphylococcus aureus bacteria with an area of inhibition of 23.7 mm and in Escherichia coli with an area of inhibition of 8.3 mm.